อาหารเสริมจากวัตถุดิบในท้องถิ่นและคุณค่าทางโภชนาการของอาหารเสริมสำหรับเด็กทารกอายุ 6 เดือน - สุรเชษฐ จินะแก้ว (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
This study aimed 1) to create complementary food recipes from local raw material for 6 months old infants 2) to analyze the nutritive values and the viscosity of complementary food recipes. The sample of law materials selected from diet diversity questionnaire of Nutrition and Food Security in Uplands of Thailand Project, which were 7 kinds including upland rice, egg, cultivated banana, pumpkin meat, leaves and stem of pumpkin, ivy gourd and sweet potato. These raw materials used to create 5 complementary food recipes for 6 months old infants, by specified proportion and estimated energy and nutrients intake for 6 months old infants per day by Thai Health Promotion Foundation, then specified amount of ingredients for complementary foods. These 5 recipes of complementary food were cooked and analyzed for nutritive values and viscosity. The data was analyzed by using descriptive statistics including mean and standard deviation. The results showed that the complementary food creating for 6 months old infant by using 7 kinds local raw materials were 5 complementary food recipes as followed: rice with cultivated banana, rice with pumpkin meat, rice with leaves and stem of pumpkin, rice with ivy gourd and rice with sweet potato. The mean of nutritive values and viscosity for each recipe per one serving size were as followed energy values were 113.40, 111.64, 106.56, 109.76 and 119.40 kilocalories respectively. Protein values were 3.51, 3.42, 3.63, 3.80 and 3.62 grams respectively. Fat values were 6.61, 6.79, 6.37, 6.66 and 7.23 grams respectively. Carbohydrate values were 9.96, 9.21, 8.68, 8.66 and 9.96 grams respectively. Ash values were 0.05, 0.46, 0.46, 0.42 and 0.52 grams respectively. Moistures values were 89.42, 95.12, 110.87, 100.46 and 88.67 grams respectively. Calcium values were 27.89, 27.08, 33.02, 38.05 and 28.35 milligrams respectively. Iron values were 1.02, 1.04, 1.09, 1.12 and 1.06 milligrams respectively. Viscosity values were 3,290, 4,239, 3,107, 2,437 and 4,445 centipoise respectively.